Production of Recombinant Human Protein C In Vitro and In Vivo by Muscle Cells - Türkay, Ataç; Wang, Jian-Min; Kurachi, Kotoku (Thrombosis and Haemostasis, 1999)
Protein C plays a key role in a natural anticoagulation mechanism, and is also implicated in fibrinolytic and anti-inflammatory functions. Here we describe the production of biologically active human protein C by muscle-targeted gene transfer. Human protein C expression vectors were designed and constructed to produce human protein C in skeletal muscle cells. These vectors were tested in transient and stable transfections of SCID mice myoblasts. Stably transfected cells produced as high as 2.27 μg/106 cells/day. Human protein C produced had a relative activity of 92 ± 8% compared to the plasma derived human protein C, and was composed of α and β forms, 69% and 31%, respectively. After implantation of stably transfected myoblasts into the hind limb muscles of SCID mice, systemic stable production of human protein C in a range of 31-116 ng/ml serum was obtained up to at least 2.5 months.Current address: J. Wang, Department of Hematology, Changai Hospital, 174 Changai Road, Yangpu District, Shangai 200433, China